(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2019)
The Conventional farming that is practiced in India are insufficient in satisfying as the demand is expanding day by day for agricultural products because of expanding population, Therefore, farmers are in high pressure, even despite of efforts, resources, labor, productive output are not getting for farmers. One way to deal with beat this issue is build up a smart system with less cost means by which the wastage of resources and labor necessity could be cut down and in the meantime the farming profitability would be expanded in quality as well quantity. This paper introduces Smart Farming which is one of the applications of Internet of Things (IOT) and uses Wireless Sensor Networks as transmission technology. The main aim of this paper is to reduce the wastage of water, real time monitoring of crop field and sending data to cloud for future references and text messages are send farmers about the field. Smart System is developed using GSM technology and Data is stored in AWS.